1971
DOI: 10.3382/ps.0500820
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Choline Supplementation of Diets for Growing Pullets and Laying Hens

Abstract: A CHOLINE deficiency is readily produced in chicks by feeding a diet low in choline or certain choline precursors. The effect of choline deficiency in laying hens, however, is less clear. McCollum et al. (1912) fed a diet containing 70 parts ground polished rice previously extracted with hot alcohol and 30 parts of dried skimmed milk to laying hens and found that more lecithin was present in eggs produced by these hens than had been consumed in the diet. Therefore, these investigators concluded that large am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
6

Year Published

1973
1973
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 16 publications
(12 reference statements)
2
14
0
6
Order By: Relevance
“…2). Os resultados de peso corporal estão de acordo com Nesheim et al (1971) e Tsiagbe et al (1982), os quais não observaram efeitos de dietas com e sem suplementação de colina para as aves Leghorn brancas. O mesmo foi descrito por Tsiagbe et al (1982) et al (1982), os quais comprovaram haver aumento de consumo quando aumentada a suplementação de colina na dieta.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…2). Os resultados de peso corporal estão de acordo com Nesheim et al (1971) e Tsiagbe et al (1982), os quais não observaram efeitos de dietas com e sem suplementação de colina para as aves Leghorn brancas. O mesmo foi descrito por Tsiagbe et al (1982) et al (1982), os quais comprovaram haver aumento de consumo quando aumentada a suplementação de colina na dieta.…”
Section: Resultsunclassified
“…Após oito semanas de idade, essas aves são capazes de sintetizar toda a colina exigida para ótima produção de ovos. Entretanto, quando as aves consomem ração de crescimento com adição de colina, faz-se necessária a suplementação da ração de postura para maximizar a produção de ovos (Nesheim et al, 1971;Tsiagbe et al,1982;Leeson e Summers, 2001). …”
unclassified
“…The choline requirement as demonstrated by growth that was better gained when the diet containing 3467 kcal ME/Kg diet, while the requirement for safeguard against perosis was greater to be about 1900 ppm (Fritz et al, 1967). Nesheim et al (1971) showed that choline supplementation reduced hepatic fat content compared to control; however no improvements in weight gain for pullets fed corn-soy diet supplemented with choline during 8-20 weeks of age. Agricultural Research Council, 1975 showed that the growing poultry chicks have a requirement for choline of around 1300 mg/kg diet (ARC, 1975).…”
Section: Choline As Growth Enhancermentioning
confidence: 99%
“…Yumurta t(lvuklarının önemli miktarlarda kalİn sentezledikleri bilinmektedir (5,9). Bazı ar<ıştırıcılar (5,8,9), bu biyosentezin hayvanın tüm kolin \"(~metil grupları ihtiyacını tam olarak karşılayabil-diğini belirtirlerken, bazıları da (10, 14, 18) karşılayamadığını da kaydetmektedicler.…”
Section: Introductionunclassified
“…Bazı ar<ıştırıcılar (5,8,9), bu biyosentezin hayvanın tüm kolin \"(~metil grupları ihtiyacını tam olarak karşılayabil-diğini belirtirlerken, bazıları da (10, 14, 18) karşılayamadığını da kaydetmektedicler. Araştırmalardaki son uçların farklı olması, tavuğun canlı ağırlığı, \'('rimi.…”
Section: Introductionunclassified